Policies that Address Sustainable Landscaping Practices - Marisa Romero; Mark E. Hostetler (EDIS, 2007)
Circular 1519, a 10-page document by Marisa Romero and Mark E. Hostetler, compiles and summarizes four city and county ordinances that promote sustainable development at the landscaping development level. Includes references. Published by the UF Department of Wildlife Ecology and Conservation, May 2007.